A Conceptual Framework: The Effect Of Waqf Management’s Performance And Religiosity On Individuals’ Intention To Contribute In Cash Waqf - Mohammed Abobakr Alhaddar; Nurshamimitul Ezza Ramli; Nur Shuhada Kamarudin; Mohamad Yazis Ali Basah (Universiti Sains Islam Malaysia, 2024)
Date: 9 September 2021 Platform: MSTeams, USIM Nilai, Negeri Sembilan, Malaysia.